Outcome of three common bariatric procedures in the public sector. Issue 11 (12th April 2016) - Clough, Anthony; Hamill, Daniel; Jackson, Shane; Remilton, Michael; Eyre, Rosemarie; Callahan, Rosie
Abstract : Background: In Australia, over 90% of bariatric surgery is performed in the private sector by paying patients with health insurance. The demand for government funded services is overwhelming and data are needed on the efficiency, safety and effectiveness of the current range of bariatric procedures in a public hospital setting. The aim of this study was to document medium term outcomes of gastric banding (laparoscopic adjustable gastric banding (LAGB)), gastric bypass (Roux‐en‐Y gastric bypass (RYGB)) and sleeve gastrectomy (SG) in a publicly funded programme. Methods: Primary cases with minimum 18 months' follow up were included. Hospital usage, complications, weight loss and co‐morbidity outcomes were compared. Results: A total of 229 patients (125 LAGB, 42 RYGB, 62 SG) were included. Mean weight (body mass index) for LAGB, RYGB and SG was 130.6 (46.3), 137.2 (50.5) and 162.7 (55.2) kg (kg/m 2 ), respectively ( P < 0.001). Operative time and hospital stay were longest for RYGB and intensive care stay was longest for SG. Major complications occurred at 0.0%, 11.9% and 12.9% ( P < 0.001) and major reoperations occurred over 5 years 11.2%, 21.4% and 6.5% ( P = 0.064). Mean (standard deviation) excess weight loss was 29.9% (33.1), 75.7% (31.8) and 52.7% (19.7) with mean follow up of 3.6 years and 79.0% complete data. Conclusions: In our public bariatric programme, LAGB patients perform relatively poorly. An increased focus on SG may be appropriate as weight loss is more reliable, major reoperation rates are low and follow up less important. Our experience should be useful for those considering how best to structure and fund a public bariatric programme.